L.M. Montgomery's Anne of Green Gables. Fire & dew [videorecording (DVD)] - Ballentine, Ella, 2001-; Botsford, Sara, 1951-; Sheen, Martin; Haytaoglu, Drew; Montgomery, L. M. (Lucy Maud), 1874-1942 (PBS, 2018)
In the third installment of this new adaptation of L.M. Montgomery's novels, Anne Shirley, now a young adult, leaves Green Gables to attend Queen's College, preparing to be a teacher. Facing a difficult choice and being overwhelmed by loneliness, Anne finds a silver lining.